Who is most afraid of crime in Iceland? - Jónasson, Jónas Orri; Gunnlaugsson, Helgi (School of Social Sciences, 2023)
Research on the fear of crime and the public’s perception of its own safety has been prominent in criminology. In this article answers will be sought as to whether the factors which have been found in other countries also affect fear of crime and public safety in Iceland. What social groups are most affected by fear of crime? Is public safety influenced by crime victimization experience? How does public safety in Iceland compare with other nations? The data is based on an online survey conducted by the Social Sciences Research Institute in early 2012 and four other surveys conducted in the time period 1989-2002. Moreover, international comparison will be performed utilizing the findings of the ICVS project which Iceland took part in. The main findings show that overall the same factors affect public safety in Iceland as has been the case elsewhere. Females, older citizens and urban residents are most affected by fear of crime. Experience of crime victimization does not seem to influence fear of crime. Public safety is high in Iceland in comparison to other nations and seems to be increasing since the first study was conducted in 1989. Rannsóknir á ótta fólks við afbrot og mat á eigin öryggi hafa verið áberandi í afbrotafræðinni á síðustu áratugum. Í greininni er leitað svara við því hverjir það eru sem einna helst óttast afbrot og hvers vegna. Er öryggiskennd þeirra sem orðið hafa fyrir afbroti minni en þeirra sem enga reynslu hafa af afbrotum? Hver er öryggiskennd Íslendinga í samanburði við nágrannaþjóðir okkar? Rannsóknargögnin byggja á netmælingu sem framkvæmd var í byrjun árs 2012 og á eldri mælingum frá tímabilinu 1989-2002. Jafnframt er stuðst við alþjóðlega mælingu á öryggiskennd (ICVS) sem Ísland tók þátt í. Helstu niðurstöður eru þær að sömu þættir virðast hafa áhrif á öryggiskennd Íslendinga og fundist hafa erlendis. Konur, eldra fólk og íbúar á höfuðborgarsvæðinu óttast afbrot frekar en aðrir og aukin menntun virðist draga úr ótta. Reynsla af afbrotum hafði ekki áhrif á öryggiskennd. Öryggi ...